Comparison of Mixing Performance of HB Impeller as Large Paddle Impeller - Haruki Furukawa; Takeru Tanaka; Yoshihito Kato (International Journal of Chemical Engineering)
Several large paddle impellers developed by Japanese companies are recognized for their excellent mixing performance across a wide range of fluid viscosities. Consequently, they are utilized in mixing operations involving changes in fluid physical properties, such as polymerization reactions. However, the mixing performance of various large paddle impellers has not been evaluated under identical power consumption conditions. The authors compared the mixing performance of various large impellers under the same power consumption and elucidated the mixing efficiency of a newly developed home base impeller (HB impeller). A decolourization method using iodine and sodium thiosulphate was used to evaluate mixing performance, and a torque meter was used to measure mixing power consumption. The HB impeller demonstrated superior and stable mixing performance over a wide range of Reynolds numbers, particularly in the absence of baffles.